2014
DOI: 10.4304/jltr.5.5.1033-1041
|View full text |Cite
|
Sign up to set email alerts
|

Learning Devices Development on Descriptive Writing for Foreign Language Based on Berlo’s SMCR Communication Model of Secondary School Student

Abstract: This research and development study aims to develop a product in the form of German descriptive writing learning device based on SMRC Berlo communication for Senior High school. The study procedure follows the first the phases of Thiagrajan 4-D Development Stage: (1) defining Stage; (2) designing Stage; (3) developing stage; (4) disseminating stage. This research involved senior secondary school teachers and students during the defining and developing phases. Besides, experts were involved during the validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Likewise with the research conducted by [28] in class VII students of SMPN I Sumber Jaya, West Lampung, that based on the results of pre-research (observation) in writing description text, there are still many students who need to improve their understanding of the description text. The research of [36] found that students did not have the basic ability to write in German well, this bad condition would positively inhibit the achievement of learning outcomes in student writing skills, especially in writing description texts. This is in line with the research conducted by [48] that first, the problem of students is the lack of vocabulary.…”
Section: International Journal Of Recent Technology and Engineering (mentioning
confidence: 99%
“…Likewise with the research conducted by [28] in class VII students of SMPN I Sumber Jaya, West Lampung, that based on the results of pre-research (observation) in writing description text, there are still many students who need to improve their understanding of the description text. The research of [36] found that students did not have the basic ability to write in German well, this bad condition would positively inhibit the achievement of learning outcomes in student writing skills, especially in writing description texts. This is in line with the research conducted by [48] that first, the problem of students is the lack of vocabulary.…”
Section: International Journal Of Recent Technology and Engineering (mentioning
confidence: 99%
“…Based on the results of observations and documentation of the learning instruments used by grade V teachers in 5 elementary schools in Grobogan Regency, among others: 1) SDN 3 Nambuhan, SDN 9 Purwodadi, and SDN 1 Kedungrejo in Purwodadi Regency; 2) SDN 3 Tunggak in Toroh Subdistrict; and 3) SDN 1 Monggot in Geyer Subdistrict, it was ascertained that there were several facts, including learning instruments commonly used by teachers such as Syllabus, Lesson Plans, Teaching Materials, and Assessment. The purpose of designing learning instruments (Syllabus and Lesson Plans) is to describe the procedure in regulating learning to achieve a basic competency set in achieving competence [6]. Learning instruments commonly used by teachers do not support Higher Order Thinking Skills (HOTS).…”
Section: Learning Instruments Used By Elementary School Teachers In Gmentioning
confidence: 99%
“…Teaching materials are needed that make it easier for students to understand the concepts of the materials. It can be achieved by means of teaching materials equipped with pictures and illustrations that can guide students to understand the concept [6].…”
Section: Teaching Materialsmentioning
confidence: 99%
“…It is estimated that writing materials requiring students' senses when practicing writing can direct students to write quality descriptive texts. Therefore, learning takes place and communication will be effective [6].…”
Section: Literature Reviewmentioning
confidence: 99%